2003
DOI: 10.1091/mbc.e03-04-0229
|View full text |Cite
|
Sign up to set email alerts
|

Sec3p Is Needed for the Spatial Regulation of Secretion and for the Inheritance of the Cortical Endoplasmic Reticulum

Abstract: Sec3p is a component of the exocyst complex that tethers secretory vesicles to the plasma membrane at exocytic sites in preparation for fusion. Unlike all other exocyst structural genes, SEC3 is not essential for growth. Cells lacking Sec3p grow and secrete surprisingly well at 25 degrees C; however, late markers of secretion, such as the vesicle marker Sec4p and the exocyst subunit Sec8p, localize more diffusely within the bud. Furthermore, sec3Delta cells are strikingly round relative to wild-type cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
127
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(139 citation statements)
references
References 47 publications
12
127
0
Order By: Relevance
“…A more direct role for Sec8p in ER inheritance seems likely because the exocyst interacts genetically and physically with the ER translocon (30-32) and probably mediates an early docking stage of ER inheritance (33, 34). As described above, other investigators reported that ER inheritance was compromised by deleting the exocyst subunit Sec3p (22). The sec8-599 mutation probably has a similar effect but has the advantage of being tolerated in our strain background.…”
Section: Truncating the Sec8p Subunit Of The Exocyst Produces Small Bsupporting
confidence: 67%
See 2 more Smart Citations
“…A more direct role for Sec8p in ER inheritance seems likely because the exocyst interacts genetically and physically with the ER translocon (30-32) and probably mediates an early docking stage of ER inheritance (33, 34). As described above, other investigators reported that ER inheritance was compromised by deleting the exocyst subunit Sec3p (22). The sec8-599 mutation probably has a similar effect but has the advantage of being tolerated in our strain background.…”
Section: Truncating the Sec8p Subunit Of The Exocyst Produces Small Bsupporting
confidence: 67%
“…Thus, mutants defective in ER inheritance also should have defects in the inheritance of both early and late Golgi cisternae. It became possible to test this model when S. cerevisiae mutants defective in ER inheritance were identified (21)(22)(23). Surprisingly, Golgi inheritance in these mutants was found to be normal (21)(22)(23).…”
Section: Yeast ͉ Organelle ͉ Mitosismentioning
confidence: 99%
See 1 more Smart Citation
“…Six subunits of the so-called exocyst complex are preassembled on secretory vesicles that contain the Rab GTPase Sec4 [53]. Other exocyst components, Sec3 and Exo70, are localized at the target site possibly via direct interaction with Rho GTPases [54,55], although the extent to which this localization contributes to polarized secretion is still being debated [56]. Completion of exocyst formation could thus tether secretory vesicles at the plasma membrane to enable fusion.…”
Section: Exocytosismentioning
confidence: 99%
“…Completion of exocyst formation could thus tether secretory vesicles at the plasma membrane to enable fusion. There appears to be some separation of duty between Sec3 and Exo70, where the latter is required for secretion of a specific class of secretory vesicles that are important early steps in bud formation [57], whereas Sec3 has an important role in inheritance of the cortical ER in the bud [55]. In the vesicle fusion reaction Sec4 facilitates the formation of a SNARE-complex between the v-SNAREs Snc1 and Snc2 and the t-SNAREs Sso1, Sso2 and Sec9 [58].…”
Section: Exocytosismentioning
confidence: 99%